Upregulated circRNA_102231 promotes gastric cancer progression and its clinical significance. Issue 1 (1st January 2021) - Yuan, Gaofeng; Ding, Wenwen; Sun, Bingjie; Zhu, Lin; Gao, Yuewen; Chen, Lulu
ABSTRACT: Circular RNAs (circRNAs) are a type of endogenous non-coding RNAs implicated in cancer progression. This study explored the expression levels, clinical implication and possible molecular mechanism of circRNA_102231 in gastric cancer (GC). Gene Expression Omnibus (GEO) was used to analyze differentially expressed circRNAs. CircRNA_102231 expression was verified by qRT-PCR in GC tissues and plasma. The effects of circRNA_102231 was tested by CCK-8, colony formation, EdU and Transwell assays and xenograft tumor model. RNA pull-down and immunoprecipitation (RIP) assays were used to analyze the interaction between circRNA_102231 and IRTKS. CircRNA_102231 expression was significantly upregulated in GC tissue and plasma samples, which can be used as a biomarker for GC diagnosis and prognosis. The function assays showed that circRNA_102231 knockdown inhibited GC cell proliferation and invasion both in vitro and in vivo . CircRNA_102231 was able to bind to IRTKS, increasing IRTKS protein stability, leading to GC progression. Overexpression of IRTKS effectively rescued the reduced cell viability and invasion caused by silencing of circRNA_102231. In sum, our data demonstrate that circRNA_102231 is a novel oncogene in GC and acts as a potential biomarker and therapeutic target for GC patients. Abbreviations circRNAs: circular RNAs; GC: gastric cancer; GEO: Gene Expression Omnibus; RIP: RNA immunoprecipitation; DEGs: differentially expressed genes